Developing Peacebuilding Learning as an Integral Component of Diaconal Practice - Prosvirnina, Oksana (Diaconia, 2024)
This article discusses the experiences of and reflections on a one-year learning programme on peacebuilding, titled "Peacebuilding Towards Convivial Life Together". The programme was specifically designed by interdiac (International Academy for Christian Social Action and Diaconia, Central and Eastern Europe) and its partner-organisations. The international group of learners in the programme consisted of grassroot practitioners in the field of diaconia, where peacebuilding is not their primary focus. Nevertheless, diaconia can play an important role in laying the foundations for peaceful convivial living by intentionally fostering receptive relationships with and between people, who are service users. The article explores the conceptual foundation and significance of "horizontal peacebuilding" through the lens of the concepts of "everyday peace" (Mac Ginty) and "conflict transformation" (Lederach). It emphasises that horizontal peacebuilding is an essential component of diaconal practice and should be understood as a process of continuous learning from the different ‘other’ and from the context. The overarching aim is to transform situations by reshaping relationships in alignment with the diaconal values of seeking justice and reconciliation. The article points out that reaching this aim through mutual learning with service users can be a transformative experience for the diaconal practitioner too. Furthermore, the article presents the framework of the learning programme, its learning goals and key elements for peacebuilding learning as integral part of diaconal practice. It highlights the advantage of "liberative pedagogy" for in-service peacebuilding learning. Finally, it proposes relevant learning activities that can support the development of the practice of diaconal engagement with local communities.